The diagnostic value of lymphocyte profiling for infectious mononucleosis and mycoplasma pneumoniae pneumonia - Shen, Xuan; Li, Wenya; Qi, Jijin; Zhong, Qing; Zhang, Yaoyun; Sun, Tianyu; Shi, Siqi; Zhang, Liang; Su, Jing (Frontiers in Pediatrics, 2025)
BackgroundInfectious mononucleosis (IM) and mycoplasma pneumoniae pneumonia (MPP) are common pediatric diseases that can easily trigger immune responses. This study aims to detect peripheral blood lymphocyte subsets through flow cytometry and explore the diagnostic value in IM and MPP.MethodsThis retrospective study using electronic medical records included a total of 86 children with IM, 150 children with MPP, and 120 healthy volunteers. Lymphocyte subsets in peripheral blood were quantitatively detected by flow cytometry, covering lymphocyte ratio, CD8+, CD4+, CD3+, CD4/CD8, CD19, and CD16 + cells. The diagnostic value of these markers was analyzed using receiver operating characteristic (ROC) curve.ResultsCompared with the HC and IM groups, the MPP group had a significantly lower lymphocyte ratio (P < 0.01). In the MPP group, CD8 + and CD3 + lymphocyte proportions were significantly reduced (P < 0.01), while CD4+/CD8 + ratio, CD4 + and CD19+ B cell levels were significantly higher than those of the IM and HC groups (P < 0.01). In the comparison between MPP and IM, ROC analysis showed that CD3+ T cells (AUC = 0.931), CD3 + CD8+ T cells (AUC = 0.989), CD4/CD8 ratio (AUC = 0.996), CD3 + CD4+ T cells (AUC = 0.992), lymphocyte ratio (AUC = 0.925), and CD19+ B cells (AUC = 0.978) all had excellent diagnostic value.ConclusionPeripheral blood lymphocyte subset analysis could serve as a precise and efficient diagnostic tool to directly distinguish between MPP and IM.